2024
DOI: 10.1109/access.2020.3039953
|View full text |Cite
|
Sign up to set email alerts
|

QoEMultiSDN: Management of Multimedia Services using MPTCP/SR in Softwarized and Virtualized Networks

Abstract: 5G networks are set to empower new user experiences for multimedia streaming services by offering high data rates and low latency. The rapid growth of multimedia services, such as video streaming services over future softwarized 5G networks, poses great challenges for both service providers and network operators regarding service provisioning with high Quality of Experience (QoE). Network evolution towards Software Defined Networking (SDN) and Network Function Virtualization (NFV) provides new opportunities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Barakabitze et al [35] proposed QoEMultiSDN, a novel QoE-aware management mechanism that uses multiPath-TCP/segment-routing (MPTCP/SR) techniques to explore information from both client and network sides in SDN/NFV networks. To optimize E2E DASH service delivery to users, QoEMultiSDN employs QoE-based multisource routing and QoE optimization, and (b) multipath protection and dynamic link-failure-free approaches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Barakabitze et al [35] proposed QoEMultiSDN, a novel QoE-aware management mechanism that uses multiPath-TCP/segment-routing (MPTCP/SR) techniques to explore information from both client and network sides in SDN/NFV networks. To optimize E2E DASH service delivery to users, QoEMultiSDN employs QoE-based multisource routing and QoE optimization, and (b) multipath protection and dynamic link-failure-free approaches.…”
Section: Related Workmentioning
confidence: 99%
“…The role of ISPs in a network virtualization environment (NVE) is divided into two categories: (a) service providers (SP) who implement different heterogeneous network archi-tectures and network protocols on VNs composed of physical network resources that are leased from one or more IPs, and (b) IPs that deploy and maintain physical network resources such as links, routers and switches [53]. Survivability in NVEs from previous works [53], including our recent papers [35], [54] where we propose multipath protections and dynamic link recovery in softwarized 5G networks using segment routing has only been considered for a single InP environment. In this study, we considered a collaboration/negotiation approach for multi-IPs as shown in Fig.…”
Section: Virtual Network Survivability and Qoe-based Pricing Model In...mentioning
confidence: 99%
“…The virtualized and softwarized network infrastructure in 5G/6G networks allows flexible deployment of the QoE monitoring solution using SDN and NFV but security, reliability, scalability and placement of the QoE monitoring solutions remain open questions for the research community [226], [260]- [262]. Furthermore, the cost-effectiveness such OPerational Expenditures (OPEX) and CAPital EXpenditures (CAPEX) for deploying QoE monitoring solutions in the next-generation 5G/6G networks using softwarized/virtualized probes remains an open challenge and question [12], [218], [263]- [265].…”
Section: B Qoe Monitoringmentioning
confidence: 99%
“…There are many studies that propose video streaming services over SDN in the literature. In one group of studies, SDN is utilized for selection of suitable streaming paths to transfer video packets from the server to the clients, thanks to the flexibility of SDN on determining flow routes [33], [34], [35] [36]. Network resources and bandwidth allocation strategies which consider parameters specific to HAS systems are also studied widely in the literature [37], [38], [39], [10].…”
Section: B Has Architectures Based On Sdn and Sandmentioning
confidence: 99%